Native lagomorphs facilitate noxious weeds in a semi-arid rangeland - Garrett, Shantell M.; Chigbrow, Darrel; du Toit, Johan T. (Frontiers in Ecology and Evolution, 2023)
Rangeland management has traditionally focused on the grazing effects of livestock, or on wild ungulates because they are potential competitors with livestock. However, herbivory by smaller herbivores, such as lagomorphs, could play a much greater role in shaping the plant community than is commonly thought. Being selective feeders with high mass-specific metabolic rates, we hypothesized that lagomorphs impose an herbivory regime on the rangeland that differs from that of ungulates and drives the plant community towards a different composition. We used an 8-year exclosure experiment with three plot types (complete exclosure, partial exclosure, open rangeland), each 5.95 m 2 , to separate the effects of grazing by lagomorphs (jackrabbits and cottontails) from the effects of the large grazers (mainly cattle and bison) on vegetation structure and plant community composition. We replicated the experiment across 20 sites in a semi-arid rangeland in the western US. The plant community in the complete exclosure plots (lagomorphs and ungulates excluded) developed a five-fold greater standing crop of grass than the open rangeland, but supported the lowest biomass, density, and aerial cover of forbs. Partial exclosure plots (ungulates excluded, lagomorphs included) developed a community with higher forb phytomass (33.6% increase relative to open rangeland) and lower forb species richness (16.4% decrease relative to open rangeland). This effect was mainly caused by the encroachment of noxious weeds, including Salsola tragus (prickly Russian thistle/tumbleweed), which covered up to 37% of the ground in plots that lagomorphs had exclusive access to. We infer that selective grazing by lagomorphs facilitates noxious weeds that are elsewhere controlled to some extent by (a) the coarse grazing and trampling effects of large ungulates and (b) competition with native herbaceous species. For semi-arid rangelands that have been degraded by livestock grazing, our complete and partial exclosures show that a reduction in stocking rate might not return the rangeland to its former state due to a hysteresis effect resulting from the facilitation of noxious weeds by lagomorphs. Rangeland management should be informed by an understanding of the entire food web, which includes the direct and indirect grazing effects of small herbivores such as lagomorphs.